The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.15384/kjhp.2019.19.4.196
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Pulmonary Function and Serum Uric Acid Level in the Korean Population

Abstract: Background: Forced vital capacity (FVC), forced expiratory volume in the first second (FEV1), and the ratio of FEV1 to FVC (FEV1/FVC) are considered as the major spirometry parameters. Serum uric acid is associated with increased risk of gout and cardiovascular disease. We analyzed the relationship between pulmonary function and serum uric acid level in the Korean men and women. Methods: This study was based on the data collected during the 2016 Korea National Health and Nutrition Examination Survey (KNHANES V… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…Although the differences did not attain statistical significance, the data indicate that uric acid may play a pro-inflammatory role in terms of LF. In another cross-sectional study, significant negative correlations were observed between the serum uric acid level and LF in both male and female 54 . The pro-inflammatory effects of uric acid may compromise the LF of non-smokers, as discussed above.…”
Section: Discussionmentioning
confidence: 86%
“…Although the differences did not attain statistical significance, the data indicate that uric acid may play a pro-inflammatory role in terms of LF. In another cross-sectional study, significant negative correlations were observed between the serum uric acid level and LF in both male and female 54 . The pro-inflammatory effects of uric acid may compromise the LF of non-smokers, as discussed above.…”
Section: Discussionmentioning
confidence: 86%